“implementación de voz sobre ip en la universidad de Guayaquil - ciudadela universitaria Dr. salvador allende y facultades remotas” - Arias Junco, Oswaldo (2010)
This project provides a solution to the problem that currently exists in the internal and external communications at the University of Guayaquil. Based on the needs presented by the establishment, has taken into account the priority of eliminating external wiring laying fiber underground building on already installed, in addition to adding several services that will enhance the economic and technological institution, and one of them is the implementation of Voice over IP. Which will improve the quality of existing services and implement new services, which offer to improve the quality of communications between schools and reduce costs as providers of services that are used today. In addition to creating a contingency which will be used in case of default communications present an inconvenience and control as security for communications.